The Impact of Fear of Missing Out on Impulsive Buying: A Study on the Twin Date Shopee Event in Indonesia - Ghaniyah, Salmaa Hasna (International Journal of Business Studies, 2024)
This study explores how the Fear of Missing Out (FOMO) affects impulsive buying during Shopee's Twin Date event in Indonesia. Employing the dimensions of a modified FOMO instrument, it scrutinizes the behavior of Shopee consumers in Indonesia when encountering this promotional event. The primary objective is to dissect customers' FOMO and its repercussions on impulsive purchases within Shopee Indonesia's twin date event, utilizing a modified set of indicators derived from prior research. Data was gathered through a well-organized survey given to 260 Shopee customers who participated in the Twin Date event. The study utilized Partial Least Squares Structural Equation Modeling (PLS-SEM). The result of this study reveals that FOMO significantly influences impulsive buying. However, this study's limitation is its exclusive focus on the impact of FOMO on impulsive buying. It overlooks other variables like price, product quality, brand trust, and consumer preferences, which also play pivotal roles in influencing consumer purchasing behavior. These factors must be revised to ensure a comprehensive understanding of consumer behavior on e-commerce platforms. Thus, the study underscores that alongside technical and functional aspects, FOMO reflects its contribution to impulsive buying during promotional events such as Shopee's twin date event.